Commissioning of ThomX Compton source subsystems and demonstration of 10^{10} x-rays/s - Muath Alkadi; Manuel Alves; Manar Amer; Loic Amoudry; Didier Auguste; Jean-Luc Babigeon; Michel Baltazar; Alain Benoit; Alexandre Blin; Marco Bonanzingamarco; Jean Bonenfant; Julien Bonis; et al. (Physical Review Accelerators and Beams)
ThomX is a compact x-ray source based on Compton scattering, installed at IJCLab (Laboratoire de physique des 2 infinis-Irène Joliot-Curie) in Orsay. The machine uses a small electron storage ring and an intense laser pulse stored in a high-finesse optical cavity. This article describes the various subsystems of the machine and their initial results of the commissioning, which began in mid-2021. This first commissioning phase led to the production of 10^{10} x-rays/s with an on-axis energy of 45 keV. The main steps to be taken to reach the nominal flux are outlined at the end.